Pengaruh Corporate Social Responsibility, Sales Growth, dan Profitabilitas Terhadap Tax Avoidance - Januari, Desak Made Dwi; Suardikha, I Made Sadha (E-Jurnal Akuntansi, 2019)
Effective Tax Rate (ETR) is used in the measurement of tax avoidance which shows the income tax expense paid by the company from the total income before tax obtained by the company. The population used in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2014-2017 with a total of 159 companies. The method of determining the sample in this study is a non-probability sampling method with a purposive sampling technique. The number of samples in this study is 36 annual report observations from 9 manufacturing sector companies that have been listed on the Stock Exchange in 2014-2017. The technique analysis used in this study is multiple linear regression. Based on the results of the analysis, it can be concluded that CSR has a negative effect on tax avoidance, sales growth has positive effect on tax avoidance, and profitability does not affect tax avoidance. Keywords: Tax avoidance, corporate social responsibility, sales growth, dan profitability